Automobile Industry Supply Chain in Thailand - Itoh, Munehiko (Kobe University Social Science Research Series,, 2018)
This research focuses on the process of growth in the automobile industries in the ASEAN region. ASEAN is drawing attention both from the vantage point of its position as an automobile-producing region and as a potential automobile market. Thailand in particular has long treated automobile production as a national strategy, and this research puts considerable focus on Thailand's initiatives. Since 2012, the authors have been carrying out on-site surveys and have visited many of the suppliers that form the local automobile industry; this published research represents a summary of those findings. The fields of specialty of this study's respective authors differ, so analyses have been made from a range of vectors. In particular, the focus is on the supply chain in what is generally referred to as a keiretsu.